Stochastic impact evaluation tool (SIE) to plan reforestation projects in Ethiopia - CGIAR Research Program on Water, Land and Ecosystems (2021)
WeForest now uses SIE to undertake ex-ante analyses that consider risks and uncertainties for all its Ethiopian forest restoration projects.